Acute effect of strength training on mood of patients with fibromyalgia syndrome - de Azevedo Klumb Steffens R.* (2019)
© 2019, Page Press Publications. All rights reserved.Fibromyalgia syndrome (FM) is a musculoskeletal disorder characterized by chronic pain and frequently associated changes in mood states. The aim of this study was to analyze the acute effect of strength training (ST) sessions on the mood states of patients with fibromyalgia. A total of 110 FM patients were eligible for this study. After the inclusion criteria, twenty-eight women with FM (mean age: 51.88±10.22 years) performed three sessions of ST. Each training session worked the main muscle groups and lasted 60 min. Three sets of 12 repetitions were performed with 1-min intervals between them. Outcome measures were assessed at baseline, after one session, and after three ST sessions. The Brunel Mood Scale (BRUMS) was used to assess mood states, and the Wilcoxon test was used to verify differences in mood after one and three ST sessions. The ST practice had positive effects on the patients’ mood states after a single session. Reductions in anger, mental confusion, mood depression, fatigue, and tension were observed. The results of the 3rd ST session were similar. We concluded that a single ST session was sufficient to improve the mood states of patients with fibromyalgia. l use only.